2019
DOI: 10.1016/j.bbrep.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective efficacy of thymoquinone against amyloid beta-induced neurotoxicity in human induced pluripotent stem cell-derived cholinergic neurons

Abstract: The natural antioxidant Thymoquinone (TQ) is the most abundant ingredient in the curative plant Nigella sativa seed's oil. An extensive number of studies have revealed that TQ is the most active and most responsible component for the plant's pharmacological properties. It has been documented in several studies that TQ has a wide range of protective activities and many neuropharmacological attributes. Amyloid beta (Aβ) is the major role player peptide in the progression of Alzheimer's disease (AD). Our current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
1
19
0
3
Order By: Relevance
“…Black cumin and TQ were shown to confer neuroprotection and improved disease outcomes in AD animal models. For example, in Aβ1–42 induced neurotoxicity, TQ protected cholinergic hiPSC neurons by restoring intracellular antioxidant levels and by inhibiting ROS generation, cell death, and apoptosis [ 51 ], and subsequently reduced quantal size of ready to release synaptic vesicle pools caused by Aβ1–42 [ 51 ]. Furthermore, in high fat/cholesterol diet (HFCD)-induced rats, TQ rich fraction nanoemulsion (TQRFNE) of black cumin decreased the brain Aβ fragment length 1–40 and 1–42 (Aβ40 and Aβ42) by modulating APP processing enzymes such as BACE1, PSEN1 and PSEN2 [ 52 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black cumin and TQ were shown to confer neuroprotection and improved disease outcomes in AD animal models. For example, in Aβ1–42 induced neurotoxicity, TQ protected cholinergic hiPSC neurons by restoring intracellular antioxidant levels and by inhibiting ROS generation, cell death, and apoptosis [ 51 ], and subsequently reduced quantal size of ready to release synaptic vesicle pools caused by Aβ1–42 [ 51 ]. Furthermore, in high fat/cholesterol diet (HFCD)-induced rats, TQ rich fraction nanoemulsion (TQRFNE) of black cumin decreased the brain Aβ fragment length 1–40 and 1–42 (Aβ40 and Aβ42) by modulating APP processing enzymes such as BACE1, PSEN1 and PSEN2 [ 52 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%
“…Activation of Nrf2 by either cellular redox status or pharmacological intervention leads to the up-regulation of over 250 genes encoding proteins that are involved in antioxidant defense systems, redox homeostasis, and xenobiotic detoxification [ 81 ]. Increased expression of antioxidant molecules and subsequent decline in oxidative markers by black cumin and TQ in various pharmacological effects indicate the involvement of Nrf2 activation [ 51 , 55 , 58 , 69 , 132 , 136 ].…”
Section: Molecular Mechanisms Underlying the Pharmacological Effects mentioning
confidence: 99%
“… 47 The results of other study suggested that TQ had neuro-protective potential and could exert as a promising therapeutic agent to reduce the risk of developing of AD and other neurodegenerative disorders of the CNS such as PD. 48 …”
Section: Methodsmentioning
confidence: 99%
“…Thymoquinone is the most abundant ingredient in Nigella sativa seed oil. This molecule protects human-induced pluripotent stem cell (hiPSC)-derived cholinergic neurons treated with Aβ(1-42) from cell death, oxidative stress and synaptic toxicity [98]. Thymoquinone reduces inflammation in a model of Alzheimer's disease by likely acting on the TLR pathway and NF-κB-signaling pathway [99,100].…”
Section: Cytoprotector Effects Of Vegetable Oilmentioning
confidence: 99%